FDG PET/CT features of polysaccharide-based hemostatic agent chronic inflammatory changes can mimic metastatic lesions - KOCAKAYA, DERYA; ASLAN, SEZER; BOZKURTLAR, EMİNE (My University, 2022)
Purpose To prevent hemorrhagic complications, hemostatic agents (HAs) have been widely used in recent years. The use of HAs can lead to false-positive results on postoperative imaging. There exists only 1 study in the literature evaluating these applications during surgical procedures. Therefore, we aimed to evaluate the postoperative imaging features of polysaccharide-based HAs in thoracic surgery patients who have had F-18-FDG PET/CT scans. Patients and Methods Two hundred nine consecutive patients who underwent thoracic surgery were enrolled in this study. A topical polysaccharide-based HA was applied to the surgical bed for all of the patients. The patients diagnosed with cancer were followed up with subsequent thoracic CT scans, and 42 of these patients were also imaged with F-18-FDG PET/CT, which then comprised the main study group. Due to suspicion of metastasis, 19/42 patients were reoperated or rebiopsied. The latest histopathological findings were accepted as criterion standard, and previous FDG PET/CT images were retrospectively reevaluated. Results Polysaccharide-based HAs that appear as amorphous basophilic material were identified in histopathological samples of 11/19 patients. Lymphocytes, plasma cells, and histiocytes, which formed foreign body reaction and/or foreign body granuloma, indicating the presence of chronic inflammation, were seen in all of the samples. F-18-FDG PET/CT showed increased FDG uptake in all of these lesions. Conclusions Despite the inconsistency of the literature, polysaccharide-based HAs can be demonstrated in human surgical specimens as amorphous basophilic materials even after a long time from the initial surgical procedure. These agents almost always cause chronic inflammatory changes. In addition, these agents may mimic \"false-positive\" findings on postoperative FDG PET/CT scans.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; FDG PET; CT; hemostatic agent; chronic inflammation; foreign body reaction; foreign body granuloma; false-positive assessment; POSITRON-EMISSION-TOMOGRAPHY; HEMOSPHERES MPH; CELLULOSE; MANAGEMENT; EFFICACY; SURGERY; POWDER; BRAIN